IMPLEMENTASI METODE SAW DAN TOPSIS UNTUK MENENTUKAN URGENSI PENGADUAN MASYARAKAT BERBASIS WEB DI KELURAHAN MANGGARAI - Mochammad Fauzi; Ari Syaripudin (Jurnal Publikasi Teknik Informatika, 2026)
The high number and variety of reports received by the sub-district office often result in a backlog of work and subjective assessments in determining the priority of handling. Thisl study focusesl on thel design andl implementation ofl a Decision Support Systeml (DSS) that aims to ensure an objective and systematic evaluation of the urgency of reports, thereby accelerating the decision-making process. This system integrates two Multicriteria Decision Making (MCDM) methods in a step-by-step sequence. The first step involves the application of thel Simple Additivel Weighting (lSAW) lmethod, withl the criterial of Report Type, Short-Term Impact, and Handling Level serving as an initial screening mechanism; reports that obtain a total SAW score below the threshold of 0.8 will automatically not be prioritized. After that, the second stage usesl the Techniquel for Orderl Preference byl Similarity tol Ideal Solutionl (lTOPSIS) methodl on reports that have passed the initial selection, with the criteria of Impact on Society and Level of Danger, to determine the final prioritization order. Thel test resultsl show thatl the combinationl of SAW andl TOPSIS is very effective in classifying reports with high accuracy and efficiency, separating urgent reports that require immediate handling. Itl is hopedl that thel implementation ofl this systeml can improve the efficiency and performance response of the sub-district, and significantly improve the quality of public services.